Oxidative Damage in Korean Medicine - Gunhyuk Park (Antioxidants, 2022)
Korean medicine originated in ancient and prehistoric times, as evidenced by the discovery of stone and bone needles in the North Hamgyeong Province, dating back to 3000 BC [...]